2013
DOI: 10.1007/s10528-013-9613-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition for Development of Nephropathy in Type 2 Diabetes Mellitus

Abstract: The aim of the study was to explore the association of the angiotensin-converting enzyme (ACE) gene I/D polymorphism and the methylenetetrahydrofolate reductase (MTHFR) gene C677T polymorphism with development of diabetic nephropathy in type 2 diabetes mellitus. Three groups were recruited during 2007-2011: 232 normal controls, 185 type 2 diabetics without nephropathy, and 407 type 2 diabetics with nephropathy. The ACE I/D and MTHFR C677T polymorphisms were examined using PCR and PCR-RFLP methods. We found no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
1
11
0
1
Order By: Relevance
“…Conflicting reports have been made in different populations on the association between the I/D polymorphism in the ACE gene (rs4340) and DN. Our findings are in accordance with the study in French subjects with T2DM, but they differ from most studies performed in Chinese, Japanese and Indian populations, as well as in two meta-analyses in Asian and Arab patients with T2DM [13,19,20,23,25-29]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Conflicting reports have been made in different populations on the association between the I/D polymorphism in the ACE gene (rs4340) and DN. Our findings are in accordance with the study in French subjects with T2DM, but they differ from most studies performed in Chinese, Japanese and Indian populations, as well as in two meta-analyses in Asian and Arab patients with T2DM [13,19,20,23,25-29]. …”
Section: Discussionsupporting
confidence: 82%
“…Wide inter-ethnic differences have been reported for allele/genotype frequencies of the I/D polymorphism of the ACE gene (rs4340), and these differences have been assumed to be responsible for the contradictory results among association studies in subjects with DN [13,19,20,23-26]. An association between rs4340 and DN was demonstrated in Asian populations (Japan, South India) [20,23] but not in Iran [31] and Malaysia [32].…”
Section: Discussionmentioning
confidence: 99%
“…31 A recent study found no significant association of ACE I/D polymorphism in the patients with DN in genotype, allele, dominant and recessive models. 36 This study finds significant differences in genotype and alleles when control subjects were compared with patients with DM and DN ( Table 3). The DD genotype was found to be high in both groups of patients.…”
Section: Discussionmentioning
confidence: 82%
“…Our finding was supported by Buraczynska [35] who showed that mutant T allele in TCF7L2 gene is powerfully linked to nephropathy, particularly in early inception of diabetes. Recently, Buraczynska [36] and Hussain [5] reported that T allele of TCF7L2 gene confers the possibility of developing nephropathy. On contrary, Wu [4] reported that the TCF7L2 gene was not coupled with diabetic nephropathy and the TCF7L2 gene might contribute to the etiology of nephropathy in T2DM patients in an interactive way with other genes.…”
Section: Discussionmentioning
confidence: 99%